Performance Analysis on MU-MIMO Field Test in TD-LTE System - Jinghua Kuang; Ziwei Long; Wei Deng (Dianxin kexue)
Based on TM7 single-stream and TM8 dua1-stream transmission mode，multiple antenna enhancement technology can be introduced in TD-LTE system，including uplink MU-MIMO and downlink MU-MIMO. In MU-MIMO algorithm，two terminals with space division can be paired to share the same downlink resource blocks for uplink or downlink transmission. Due to the multiplexing of time-frequency resource，the valid transmission resource can be increased remarkably，thus the gain on dua1-terminal throughput and the cell overall throughput performance can be obtained. Detailed analysis on field test of uplink and downlink MU-MIMO was given，based on the algorithm implement of TD-LTE network equipment vendors.